Experience of mothers in the care of children with type 1 diabetes - Elis Mayre da Costa Silveira Martins; Márcia Barroso Camilo de Ataíde; Denise Maia Alves da Silva; Mirna Albuquerque Frota (Rev Rene)
Descriptive qualitative study aimed to understand the experience of mothers in the care of type 1 diabetic children in a unit of Tertiary Reference in Diabetes, located in Fortaleza, Ceará, Brazil. Data were collected through semi-structured interviews with 12 mothers of diabetic children, aged 3-12 years. The results were analyzed using the techniques of thematic analysis of Bardin, with these highlighted categories: multiple feeling generated in the impact of the diagnosis; mother facing the competitiveness of affection among the children, the experience of the mother in the expansion of the locus daily care. Conclusion: the disease affects the whole family, and the burden of care falls on the mother in all aspects of the disease, professional support is necessary, once the assistance provided by the mother goes beyond the diabetic child care related to metabolic control.